Evaluasi Kinerja Karyawan dalam Perspektif Islamic Human Resource Management di Dinas Sosial Kabupaten Hulu Sungai Selatan - Wira Kusuma; Zakky Zamrudi; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze employee performance at the Social Service Office of Hulu Sungai Selatan Regency by integrating the principles of Islamic Human Resource Management (IHRM). The main focus of this research is to explore the application of Islamic values such as trustworthiness (amanah), justice (‘adl), excellence (ihsan), and responsibility in the employee performance evaluation process. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and document analysis. The findings indicate that the internalization of Islamic values plays a significant role in shaping the integrity, work ethic, and social responsibility of public servants. However, its implementation remains suboptimal, as it is still limited to the individual moral sphere and has not yet been systematically institutionalized within the assessment instruments. The study suggests that the Social Service Office should develop IHRM-based performance evaluation indicators, so that the assessment process is not only oriented toward administrative aspects but also reflects spiritual values and Islamic work ethics.